2023
DOI: 10.1186/s12936-023-04568-5
|View full text |Cite
|
Sign up to set email alerts
|

CDC light traps underestimate the protective efficacy of an indoor spatial repellent against bites from wild Anopheles arabiensis mosquitoes in Tanzania

Abstract: Background Methods for evaluating efficacy of core malaria interventions in experimental and operational settings are well established but gaps exist for spatial repellents (SR). The objective of this study was to compare three different techniques: (1) collection of blood-fed mosquitoes (feeding), (2) human landing catch (HLC), and (3) CDC light trap (CDC-LT) collections for measuring the indoor protective efficacy (PE) of the volatile pyrethroid SR product Mosquito Shield™ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Recent epidemiological trials for an transfluthrin-based passive emanator have demonstrated reductions in malaria 27 . It is likely that the clinical impact of such interventions against malaria is greater than that measured via traditional mosquito endpoints such as indoor density or human landings 7 . Evaluation of volatile pyrethroids is best conducted using assays that can capture all modes of action including semi-field studies or experimental hut trials 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent epidemiological trials for an transfluthrin-based passive emanator have demonstrated reductions in malaria 27 . It is likely that the clinical impact of such interventions against malaria is greater than that measured via traditional mosquito endpoints such as indoor density or human landings 7 . Evaluation of volatile pyrethroids is best conducted using assays that can capture all modes of action including semi-field studies or experimental hut trials 28 .…”
Section: Discussionmentioning
confidence: 99%
“…HLC is a direct measurement of human-vector contact that has not been reproduced accurately using traps 3 5 , but it has disadvantages especially with wild-field mosquitoes, as pathogen transmission could occur 5 . There is some experimental evidence that HLCs provide a reasonable proxy of human biting 6 , 7 . However, HLC measures only mosquito attack rate and is not sensitive for measuring other effects of vector control tools beyond landing inhibition 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The data used to parameterise the stable netting control strategy was gathered using WHO cone bioassays and light-traps within stables. Light traps have been observed to not effectively estimate protective efficacy for spatial repellents [35]. Considering this, and the relatively small number of vectors caught in the stable (n=25), the estimation for the reduction in biting may be inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have demonstrated reductions in malaria [24]. It is likely that the clinical impact of such interventions against malaria is greater than that measured via traditional mosquito endpoints such as indoor density or human landings [7]. Evaluation of volatile pyrethroids is best conducted using assays that can capture all modes of action including semi-field studies or experimental hut trials [25].…”
Section: Discussionmentioning
confidence: 99%
“…HLC is a direct measurement of human-vector contact that has not been reproduced accurately using traps [3][4][5], but it has disadvantages especially with wild-field mosquitoes, as pathogen transmission could occur [5]. There is some experimental evidence that HLCs provide a reasonable proxy of human biting [6,7]. However, HLC measures only mosquito attack rate and is not sensitive for measuring other effects of vector control tools beyond landing inhibition [8].…”
Section: Introductionmentioning
confidence: 99%